Recruiters' and Applicants' Reactions to Campus Interviews and Employment Decisions - Powell, Gary N.; Goulet, Laurel R. (Academy of Management Journal, 1996)
The relationship between college placement interviews and subsequent employment decisions by organizations and applicants has received scant research attention. In a longitudinal field study, we found that applicants' job choices were related to their postinterview intentions. However, organizations' job offer decisions were not related to recruiters' postinterview intentions or to their perceptions of applicants' intentions. The results offered general support for the applicability of the theory of reasoned action to the recruitment process.